An illustrated key to the New World genera of Philonthina Kirby (Coleoptera: Staphylinidae), with morphological, taxonomical and distributional notes - Chani Posse, Mariana Raquel (2014)
An illustrated key to the 29 genera of Philonthina currently known in the New World is provided, based on adult morphological characters. Updated information on the morphology, taxonomic history, bionomics and distribution of the Philonthina in the study area is also provided.